Electrochemical properties of bi-component bundle of coaxial polyacrylonitrile/ polyaniline nanofibers containing TiO2 nanoparticles. (October 2017) - Taghipoor, Fatemeh; Semnani, Dariush; Naghashzargar, Elham; Rezaei, Behzad
Electroactive actuators including materials or devices can respond to an electric field, current, or voltage with a corresponding change in their size or shape. Recent researches show an emerging interest in the electroactive polymers actuating systems because of their proper electrochemical properties for actuators and artificial muscles. The current research involves fabrication of core–sheath polyacrylonitrile (PAN)–polyaniline (PANi) nanofibers containing up to 15% TiO2 nanoparticles in core, as well as the investigation of the mechanical and electrochemical properties of the prepared nanofibrous bundles. In the first step, high electrical conductive PANi polymer was synthesized through the oxidative polymerization method. TiO2 nanoparticles were added to the core of nanofibers to improve both mechanical and electrical properties of the produced nanofibrous bundles. Synthesized PANi was used to produce aligned nanofibrous bundles comprising PAN–TiO2 (0–15%) as core and PAN–PANi as sheath with an average diameter of 199–350 nm. The structural and physical properties of nanofibrous bundles were studied by Fourier-transform infrared, scanning electron microscopy, and transmission electron microscopy techniques. Mechanical and cyclic voltammetric tests were performed on core–sheath PAN/PANi samples to evaluate the mechanical and electrochemical properties, respectively. According to the results, fabricated bundles of coaxial PAN–TiO2 / PAN–PANi nanofibers is highly recommended as a candidate for electroactive actuator because of high electrical conductivity. PAN/ PAN–PANi nanofibers demonstrate an oxidation/ reduction peak of 0.8 V with a maximum current of 14.0 × 10 −5 A related to PANi and PAN–TiO2 (10%)/ PAN–PANi has a maximum current of 11.0 × 10 −5 A with a peak at 0.8 V because of the presence of PANi.